Fusarium falciforme eumycetoma: a diagnostic challenge of a neglected tropical disease - Badarol Hisham, Noralwani; Abdul Rhani, Shaharuddin; Mohd Ali, Razana; Masri, Siti Norbaya (BMJ Publishing Group, 2024)
Eumycetoma, a subcutaneous infection caused by various fungi with pathognomonic discharging grain, is rarely reported in Malaysia. This case concerns a eumycetoma infection in an immunocompetent man who presented with progressive left foot swelling complicated with pustules, sinuses and pale grain discharge for the past year after recurrent thorn pricks. Histological findings of the grain and tissue showed foci of septate fungal hyphae. Tissue culture yielded no growth. Amplification and sequencing of the rDNA internal transcribed spacer 1 (ITS1), ITS4 and large subunit regions of the tissue identified the causative agent as Fusarium falciforme, highlighting the role of molecular diagnostic methods in identifying fungal species in eumycetoma. The patient was treated with surgical excision and oral itraconazole with excellent improvement. However, he presented again with recurrence after defaulting therapy. F. falciforme has been implicated in causing diseases in crops and sea turtles. Therefore, the One Health approach should be adopted to manage this emerging species